Exploring the structural, mechanical, dynamical, thermal, electronic, magnetic, and optical properties of monolayer WTe2 compound: First-principles study - Yadav, Sukrit Kumar; Neupane, Tejendra; Pokharel, Arpan; Khanal, Kamal; Deuba, Karan; Rijal, Om Shree; Neupane, Hari Krishna (BIBECHANA, 2025)
The potential applications of materials are determined by their existing properties. In this work, we used first-principles approach to investigate the structural, mechanical, dynamical, thermal, electronic, magnetic, and optical properties of (3×3) supercell structure of Tungsten ditelluride (WTe2) compound using GGA-PBE functional of density functional theory (DFT) method. Structural properties of WTe2 compound are studied by measuring bond lengths between the atoms in structure, and ground state energy. It is found to be structurally stable material. Electronic band structure and density of states (DOS) plot shows that the material has direct band gap p-type semiconductor. Magnetic properties of WTe2 compound are predicted by the analysis of its density of states (DOS) and partial density of states (PDOS) plots, material is found to be non-magnetic in nature. The mechanical properties of considered compound are examined by the calculations of its modulus of rigidities, elastic constants, elasticity and anisotropy index. WTe2 has ductile and anisotropic properties. Moreover, we have examined the dynamical stability of considered material through the phonon dispersion curve, it reveals that WTe2 is dynamically stable material. Based on the calculations of phonon velocities and Debye temperature, it is found that WTe2 has low value of specific heat capacity. Dielectric function, optical conductivity, absorption, transmission, and reflection coefficients of WTe2 compound are examined for the exploration of its optical characteristics. At higher photon energy region, WTe2 has transparent and anisotropic in nature, higher value of conductivity, lower values of absorption and reflection coefficient. Hence, it can be used in the fields of electronic, optoelectronic, sensing, and energy storage devices